WHO STOLE THE RAIN? THE CASE OF RECENT SEVERE DROUGHTS IN KENYA - Kioko, Musingi J.B. (European Scientific Journal, ESJ, 2013)
ï»¿ï»¿Drought is one of the major scourges of humanity with its devastations manifested in form of negative economic impacts, massive malnutrition, human miserly and death to both livestock and people. Yet drought (and its impacts) is not new and has been a subject of writing from early days and from many parts of the world. This paper discusses weather and human related causes of drought in Kenya, using a case study of the 2008-2009 and the 2011 droughts in Kenya and affecting the whole Horn of Africa whose devastating impacts are still being felt. It uses information from various sources collected in the recent past on weather and declining forest cover in Kenyaâ€™s key water towers as a possible link to the drought. The analysis show that the drought may have been caused by the ongoing climate change while the severity of the drought impacts were made worse and may be attributed to a series of events which are human related including post-election violence in 2007, failed government policies on food security leading to poverty in semi-arid parts of Kenya. The paper notes that those most affected by the drought were the pastoralists, children and women, while wildlife was not spared either. It proposes policies that promote an integrated creative approach in fighting drought related famines in Kenya which include initiating both a â€œgreenâ€ and â€œblueâ€ revolutions in Kenyaâ€™s marginal lands as a way of climate change adaptation strategies to mitigate food insecurity.